Design And Development Of Spo2, Bpm, And Body Temperature For Monitoring Patient Conditions In Iot-Based Special Isolation Rooms - Dyah Purwitosari; Bambang Guruh Irianto; Triwiyanto Triwiyanto; Phuoc-Hai Huynh (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2023)
The use of batteries as the main power source in portable equipment systems has several drawbacks, including the percentage of battery power that must be monitored so that the system is always active. Analysis of battery power efficiency is needed to determine the resistance of portable systems. This study makes a portable system for monitoring the condition of patients with infectious diseases in a special isolation room that can measure heart rate, body temperature, and oxygen saturation. The design of this device uses a 2200mAH battery as a power source on the IC TTGO ESP32 to manage data and display measurement results, the MAX30102 sensor to measure oxygen saturation and heart rate, and the MCP9808 sensor to measure body temperature. The design of this device has been tested on respondents aged 25-40 years by placing the sensor on the fingertip then the measurement results are compared with a standard device that has been calibrated. The measurement results show that the device is feasible to use because the measurement error value is ±5%. Testing the efficiency of battery power in normal mode and save mode. In normal mode, the current used in the device is 154.9 mA, while the save mode by not activating the LCD TTGO ESP32 requires a current of 126.7 mA. The results of the analysis show that using the battery in normal mode can activate the device for up to ±14 hours and in save mode for ±17 hours. This designed method is useful for measuring power efficiency in different device modes and the user knows the battery charging time at regular intervals.